Effect of drill geometry of uncoated tool when drilling titanium alloy, Ti-6Al-4V - Rashiddy Wong, Freddawati (2008)
Titanium alloys are widely used in various applications such as in aerospace industry, especially in airframes and engine components due to their high strength-weight ratio that is maintained at elevated temperature and their exceptional corrosion resistance. Nevertheless, titanium and its alloys are difficult-to-machine material due to their poor thermal properties and highly chemical reactivity. In this study, Ti-6Al-4V had been drilled using different drill point geometry under various cutting speeds and feed rate. The tools are Tool A (spiral point), Tool B (3 facet) and Tool C (4 facet). The tool life, tool wear and surface roughness were analyzed under various cutting speeds and feed rates. In this study, Type C drills outperformed Type A and B drills in terms of tool life for almost all the cutting conditions tested. At the lowest cutting speed of 50 m/min and lowest feed rate, 0.05 mm/rev, Tool C demonstrated the longest tool life, which resulted in low tool wear rate. The excellent improvement of Tool C give higher tool life compared to Tool A and Tool B when drilling at higher cutting speeds. Its due to its multi-faceted geometry and web thickness. Non-uniform flank wear, chipping and catastrophic failure were the dominant failure modes of all tools under most cutting conditions tested. These failure modes were mainly associated with adhesion, diffusion and plastic deformation wear mechanisms. Based from the results obtained, it can be suggested that Type C drill was recommended and the lower cutting speed of 50 m/min should be employed in order to achieve high performance in drilling titanium alloy, Ti- 6Al-4V.